2022
DOI: 10.1177/00472875221126428
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Mortality Anxiety: Identifying Heritage Tourism’s Role in Terror Management

Abstract: Although terror management theory has been widely studied, little research has empirically examined whether travel functions as a terror management mechanism. Thus, the present research investigated the influence of mortality anxiety on heritage tourism preference and heritage protection intention through two studies. Study 1 shows that as individuals’ general mortality anxiety increases, their tendency to search for meaning in life increases, which fosters their heritage travel preference and heritage protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 105 publications
(132 reference statements)
0
8
0
Order By: Relevance
“…Further, there have been only a few studies (Kwak and Hong, 2017; Lyu et al , 2022) that have investigated the role of travel in response to mortality salience. Our findings suggest that individuals who feel psychologically threatened use travel as an important coping strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Further, there have been only a few studies (Kwak and Hong, 2017; Lyu et al , 2022) that have investigated the role of travel in response to mortality salience. Our findings suggest that individuals who feel psychologically threatened use travel as an important coping strategy.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of the author’s knowledge, this study is the first to incorporate and empirically validate the influence of death anxiety before visitation. Dark tourism has often been sought as a form of tourism that subconsciously dampens death anxiety (Biran & Buda, 2018; Lyu et al, 2022). The present research extends this line of investigation, contributing to the understanding of pre-trip tourist behavior and building a bridge between the terror management literature and tourism literature.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…According to them, the consumption of death-related tourism products can alleviate the fear of death by enhancing the individuals’ cultural worldviews and/or self-esteem. Lyu, Wang and Wei (2022) also found that, by increasing individuals’ propensity to pursue meaning in life, mortality anxiety promotes their preference for death-related tourism. Thus, dark tourism is considered a modern, socially acceptable form of consumption to deal with death anxiety.…”
Section: Dark Tourism and Lighter Dark Sitesmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, coping strategies were developed by travelers while engaging in remote travel for work (Chevtaeva et al, 2023), engaging in dark tourism (Jordan & Prayag, 2022), encountering a mismatch between tourism expectations and experiences (Hossain et al, 2023); enduring crisis on a cruise ship (C.-D. , and developing wellbeing in the context of religious tourism (Lin & Hsieh, 2022). Coping strategies are also linked with anxiety of mortality (Lyu et al, 2023), fear of travel (D. Zheng et al, 2021), visiting a new, unfamiliar country (Wu, 2015) and age-related constraints during travel (Kazeminia et al, 2015). An extensive review of the prior literature has revealed that these existing studies did not offer a holistic understanding of how coping strategies are formulated and used by travelers, especially how travelers build such coping strategies in the aftermath of a crisis.…”
Section: Introductionmentioning
confidence: 99%